The Integration of the Curriculum of Love and Environmental Theology Concepts in Islamic Education at the Primary School Level - Ummi Qudsiyah; Khairil Anwar; Fimeir Liadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: The integration of the Curriculum of Love and Environmental Theology in Islamic Education at the Primary School Level addresses the urgent need for a holistic educational framework that fosters intellectual development, moral character, and environmental consciousness among students. Aim: This study aims to (1) determine the urgency of integrating education based on the Curriculum of Love and Environmental Theology, (2) identify conceptual models for such integration, and (3) explore the challenges and opportunities in implementing this integration within Islamic education at the primary level. Method: Using a qualitative descriptive approach with library research methods, the study analyzes various literature sources, including scholarly books, journals, and articles related to love-based education, environmental theology, and Islamic education practices. Thematic analysis was employed to extract key themes and insights. The findings reveal that integrating love and environmental theology into the curriculum is crucial for shaping students who are not only academically competent but also compassionate, socially responsible, and ecologically aware. The conceptual integration model proposed includes an interdisciplinary approach, character education emphasizing compassion and stewardship, experiential learning such as outdoor and community-based activities, and incorporation of local wisdom and Islamic values. However, implementation faces significant challenges, including limited resources and infrastructure, resistance to curriculum changes, lack of teacher training, and societal attitudes inclined toward consumerism. Despite these barriers, notable opportunities exist to advance this integration through collaborative efforts among educators, policymakers, parents, and communities. Innovative teaching methods, curriculum redesign, and the contextualization of Islamic teachings offer pathways to embed love and environmental values meaningfully into primary education. Conclusion: integrating the Curriculum of Love and Environmental Theology within Islamic Education at the Primary School Level is both necessary and feasible, offering transformative potential to produce a generation of students who are intellectually skilled, morally grounded, and environmentally conscious, ready to contribute positively to society and address global challenges.